Effects of Partial Esters on the Properties of Palm-Based Trimethylolpropane Esters - Abu Bakar, Anita (2006)
Some concerns have been raised regarding the oxidative stability of vegetable oil-based fluids. Lack of oxidative stability will increase the rate of oxidation and degradation of the oil. Oxidation causes sludge and deposits formation, clogging of oil passages and corroding the equipment that they lubricate. Earlier findings have indicated that oxidative stability is partly due to the presence of partial ester in the lubricant. The hydroxyl group present in the partial ester increases the oxidative stability of the lubricant. Thus, a wide range of palm-based trimethylolpropane esters (TMPE), which contain different percentages of partial esters, were synthesized. The palm-based TMP esters (mono esters, diesters and triesters) were esterified from palm oil methyl esters (PME) with trimethylolpropane [2-ethyl-2-(hydroxymethyl)-1,3-propanediol;TMP] and sodium methoxide (CH3ONa) as catalyst. Quantification of unreacted palm oil methyl esters (PME), monoesters, diesters, and triesters were performed using gas chromathography (GC), with a high temperature capillary column (SGE HT5), operated at a temperature gradient of 6°C/min starting from 80°C to 340°C. The influence of operating variables (temperature, pressure, molar ratio PME:TMP and catalyst amount) on diester formation were studied and analyzed. Palm oil TMP esters containing 5–30% (w/w) partial esters (monoesters and diesters) were successfully synthesized at different operating variables.